Gut Lactobacillus Level Is a Predictive Marker for Coronary Atherosclerotic Lesions Progress and Prognosis in Patients With Acute Coronary Syndrome - Gao, Jing; Wang, Jie; Zhao, Li-Li; Yao, Ting-Ting; Chen, Yang; Ma, Jing; Zhang, Xu; Wang, Jing-Xian; Wang, Yuan; Cui, Zhuang; Liu, Yin (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Gut microbiota dysbiosis can contribute to the progression of atherosclerosis. We investigated the association of the gut microbiota and the severity of coronary artery lesions and prognosis of patients with ACS. Methods: In this case-control study, 402 ACS patients and 100 controls were enrolled from June 2017 to December 2018. The number of bacterial species was determined by real-time PCR. A SYNTAX score was calculated for all ACS patients based on coronary angiography results. Results: Compared with healthy controls, the gut microbial levels in Escherichia coli., Streptococcus, and Enterobacteriaceae were significantly increased in ACS patients, while Lactobacillus level was significantly decreased. Lactobacillus level was as an independent predictor of disease severity on coronary angiography (high vs. low SYNTAX score: adjusted odds ratio [aOR] = 0.024, 95% confidence interval [CI]: 0.004-0.155) and myocardial necrosis (high vs. low cardiac troponin T (cTNT): aOR = 0.317, 95% CI: 0.099-0.914). Subsequently, higher Lactobacillus level was associated with a lower risk of all-cause death (adjusted hazard ratio [aHR] = 0.239; 95% CI: 0.093-0.617) and major adverse cardiac events (MACE) in ACS patients (aHR = 0.208; 95% CI: 0.081-0.531). After stratifying by type of ACS, higher Lactobacillus level significantly associated with the decreased risks of high SYNTAX score, all-cause death, and MACE in STEMI subgroup but not in NSTEMI and UAP subgroups. Conclusions: Lower Lactobacillus levels may indicate a higher risk of more severe coronary atherosclerotic lesions and myocardial necrosis and worse prognosis for patients with ACS, particularly in STEMI subgroup.